Effect of Butterfly Pea (Clitoria ternatea) Flower Fraction on the To-tal Leukocyte Count of Common Carp (Cyprinus carpio) - Putri, Rinata Entonnia; Sri Andayani; Seto Sugianto Prabowo Rahardjo (Department of Aquaculture, 2025)
Intensive common carp (Cyprinus carpio) farming is prone to bacterial infections such as Aeromonas hydrophila, and while antibiotics are effective, their overuse raises concerns about resistance and environmental impact. This study aimed to identify the fractions of butterfly pea flower (Clitoria ternatea) extract through phytochemical tests, UV-Vis, and FTIR spectrophotometry, and evaluate their immunostimulant potential by assessing total leukocyte counts in common carp (C. carpio). The research was conducted from December 2024 to February 2025 at the Fish Disease and Health Laboratory, Brawijaya University. Fifty Majalaya strain common carp were divided into treatment and control groups, receiving 25 ppm extract fractions. Extraction was performed using ethanol, ethyl acetate, and n-hexane, followed by fractionation via thin-layer chromatography (TLC). Leukocyte count analysis was conducted from day 0 to day 3 using microscopy. Results showed that 96% yielded the highest extract recovery (22.16%), while ethyl acetate contained the best bioactive compounds. The optimal TLC eluent was chloroform: methanol (9:1), producing distinct light green and pink spots. Fraction 5 showed the highest leukocyte increase from day 0 (0.73 × 10⁴ cells/mm³) to day 2 (0.29 × 10⁴ cells/mm³) and the lowest decrease on day 3 (0.13 × 10⁴ cells/mm³). UV-Vis spectrophotometry revealed a peak at 659 nm, indicating the presence of phenolics, flavonoids, and alkaloids. FTIR spectroscopy confirmed the presence of key functional groups, including O-H, C-H, C≡N, C=O, and C=C. These findings suggest fractionated butterfly pea flower extract as a promising natural immunostimulant for sustainable aquaculture.